Single-stage three-phase boost power factor correction circuit for AC–DC converter. Issue 1 (2nd January 2018) - Azazi, Haitham Z.; Ahmed, Sayed M.; Lashine, Azza E.
ABSTRACT: This article presents a single-stage three-phase power factor correction (PFC) circuit for AC-to-DC converter using a single-switch boost regulator, leading to improve the input power factor (PF), reducing the input current harmonics and decreasing the number of required active switches. A novel PFC control strategy which is characterised as a simple and low-cost control circuit was adopted, for achieving a good dynamic performance, unity input PF, and minimising the harmonic contents of the input current, at which it can be applied to low/medium power converters. A detailed analytical, simulation and experimental studies were therefore conducted. The effectiveness of the proposed controller algorithm is validated by the simulation results, which were carried out using MATLAB/SIMULINK environment. The proposed system is built and tested in the laboratory using DSP-DS1104 digital control board for an inductive load. The results revealed that the total harmonic distortion in the supply current was very low. Finally, a good agreement between simulation and experimental results was achieved.